MEDIA PENDIDIKAN GIZI NUTRITION CARD BERPENGARUH TERHADAP PERUBAHAN PENGETAHUAN MAKANAN JAJANAN ANAK SEKOLAH DASAR - Ni Putu Wahyuningsih; Siti Rahayu Nadhiroh; Merryana Adriani (Universitas Airlangga, 2015)
Less knowledge related to street food among primary schoolchildren is one of problem that need an attention. An effort to tackle that problem is crucial, for example by giving nutrition education through educational media. This research aims to analyze differences in knowledge after intervention with nutrition card and whiteboard. The design study used was quasi experimental with pre test – post test control group. Sample in this study was fifth grade student with 27 primary schoolchildren in each group. Intervention was conducted for 1 month consist of 8 meetings and each meeting was done for over 30 minutes. Based on mann whitney test, result shows that there was a differences in knowledge (P<0,05) after nutrition education with a nutrition card. The conclusion from this study is nutrition card could knowledge about food street among primary schoolchildren. Wider socialization of this type of education is need to be done both in schoolchildren in SDN Keputih 245 as well as other schools.Keywords: nutrition card, nutrition education, primary school children